Private Capital for Railway Development - Lawrence, Martha; Ollivier, Gerald (World Bank, Washington, DC, 2016)
China is considering ways to attract additional capital to finance investment in railways. Worldwide, private capital has been attracted to the railway sector through a range of mechanisms including: (i) private sector provision of specific rail services or assets such as rolling stock; (ii) public private partnerships; (iii) leveraging commercial value of rail assets and increased land value around stations; and (iv) debt and equity financing of railway companies. Private sector investors seek to earn a return on investment that is commensurate with the risk of the investment. Therefore one will be attracted to profitable opportunities with manageable risk. Steps China can take to attract private capital for railway development include: (i) creating a policy and legal environment that protects the interests of different types of investors in the railway sector; (ii) identifying and creating profitable railway markets and entities that are suitable for private sector investment; (iii) managing the perception of risk in railway activities and assets; (iv) promoting asset sharing opportunities; and (v) expanding public private partnerships (PPPs) in rail assets and services.